Flaps in reconstructive surgery - Caprielova, Yuri Jiménez (International Surgery Journal, 2022)
A flap is one with a persistent blood supply that does not rely on the recipient’s bed to perfuse donor tissue. Free flaps are used in a different context. Before reconstructing any wound bed, the surgeon must ensure that the receiving bed is properly prepared. The wound must be free of any necrotic or ischemic tissue. In addition, signs of infection such as local cellulitis, significant edema, or purulent drainage should have decreased. Flaps have wide applicability and choice, with an almost infinite range of flaps available to cover even the most complex defects. It is necessary to consider the aesthetic and functional results, as well as the comorbidities and possible morbidity of the donor site. The routine use of flaps has drastically expanded the surgeon’s ability to care for the injured patient. In addition, previously unresectable cancers have become resectable with the ability to offer flap reconstruction. The ability to move tissues has improved the quality of life of countless patients.